Studies of the role of sialyl Lewis X antigen and E selectin ligands in colorectal cancer - Deschepper, Fanny Marjolaine (2020)
Glycosylation alterations dysregulate multiple biological processes and are a hallmark of cancer, linked to tumorigenesis and tumour progression. The present study focuses on altered glycosylation in colorectal cancer (CRC), the third most common cancer worldwide. Increased sialylation and fucosylation are reported in CRC and associated with malignant tumour features. This increase is translated by upregulation of the sialofucosylated sialyl Lewis X (sLeX) antigen, a ligand of the endothelial E-selectin, having a potential role in metastasis. Thus, overexpressing sLeX antigen may affect the expression of E-selectin ligands and the invasion capacity of CRC cell lines. Moreover, the effect of increased sLeX antigen expression on tumour cells immunosuppressive strategies has not been clearly examined so far. To address these hypotheses, we first characterised the impact on the biology and the glycan profile of sLeX overexpression in CRC cells. The results showed improvement of cell migration and reactivity with E-selectin, upon increased sLeX expression. Then, we identified the glycoproteins immunoprecipitated with E-selectin by mass spectrometry, and our results revealed neural cell adhesion molecule L1 (L1CAM). Furthermore, we showed that the sLeX antigen overexpression by CRC cells reduces the maturation profile of dendritic cells (DCs), as inferred by a decreased expression of the antigen presenting molecule, MHC-II, and the co-stimulatory molecule, CD86. This thesis is the first to report the L1CAM ability to interact with E-selectin. Since L1CAM is known to be elevated in cancer and associated with metastasis and progression, this should contribute to better understand its action mechanism. Also, the reduced DCs maturation induced by sLeX expressing CRC cells, may diminished the capacity to appropriately engage immune response against tumour cells. Overall, these findings contribute to elucidate the role of sLeX antigen and E-selectin ligands on CRC progression, metastasis and in the tumour immune system escape strategy, proposing potential novel targets for therapeutic treatments of CRC.